Способ определения количества анализируемого вещества по цветовой шкале - Муравьев С. В. Сергей Васильевич; Гавриленко Н. А. Наталия Айратовна; Спиридонова А. С. Анна Сергеевна; Силушкин С. В. Станислав Владимирович
опубл. 10.09.11